2016
DOI: 10.1007/s11904-016-0337-5
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-Informed HIV Prevention and Treatment

Abstract: The high prevalence of trauma and its negative impact on health and health-promoting behaviors underscore the need for multi-level interventions to address trauma and its associated sequelae to improve physical and mental well-being in both HIV-infected and HIV-uninfected populations. Growing global awareness of the intersection of trauma and HIV has resulted in development and testing of interventions to address trauma in the context of HIV treatment and HIV prevention in the U.S. and globally. Despite increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 38 publications
2
66
0
Order By: Relevance
“…Increased recognition of the intersection between HIV and IPV has led to numerous calls to improve the delivery of HIV services to be more responsive to those with a history of trauma (Sales, Swartzendruber, & Phillips, 2016). Results from our study highlight aspects of the testing process that may be unique for victims of IPV and have implications for improving the quality of HIV testing in this population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased recognition of the intersection between HIV and IPV has led to numerous calls to improve the delivery of HIV services to be more responsive to those with a history of trauma (Sales, Swartzendruber, & Phillips, 2016). Results from our study highlight aspects of the testing process that may be unique for victims of IPV and have implications for improving the quality of HIV testing in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Experiences of trauma, such as IPV, can have numerous impacts on HIV risk, testing decisions, and paths for recovery (Draucker et al, 2015; Rountree, 2010; Sales et al, 2016). Providers in our study indicated that there was a need for improved awareness in both clients and providers that the experience of IPV increased an individual’s risk for acquiring HIV.…”
Section: Discussionmentioning
confidence: 99%
“…To minimise selection bias, we reviewed the articles included in the meta-analysis to ensure they met eligibility criteria. Gender and sexual orientation were considered because of underlying differences in the epidemics of HIV and trauma 30–32. Specifically, populations were grouped as women and men, and samples of HIV-infected men were further classified into men who have sex with men (MSM) and non-MSM males.…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol use was also a way to evade interpersonal relational accountability and was used by LG hunters to take advantage of young women. Alcohol and its role in increasing risk for unprotected sex is well documented among youth populations (Kiene, Barta, Tennen, & Armeli, 2009;Leston, Jessen, & Simons, 2012;Sales, Swartzendruber, & Phillips, 2016;Senior, Helmer, Chenhall, & Burbank, 2014;Shrier, Kim Harris, Sternberg, & Beardslee, 2001), as is the cultural norm of pressure on young women to engage in sexual activity, particularly if alcohol or other drugs are involved (Senior et al, 2014). However, this is the first study to document the role of alcohol in the context of LG hunters among NWT youth.…”
Section: Discussionmentioning
confidence: 88%